INOVASI HIJAU : PEMANFAATAN SAMPAH RUJAK PANTAI NATSEPA SEBAGAI PUPUK ORGANIK CAIR BERBASIS PEMBERDAYAAN PEMUDA NEGERI SULI - Ludia Siahaya; Thomas M. Silaya; Yulianus D. Komul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
Natsepa Beach is a leading tourist destination in Maluku, renowned for its natural beauty and rujak culinary delights. Research data shows that the average waste per visitor to Natsepa Beach is 0.12 kg per person per day, with organik waste amounting to 0.11 kg per person per day. With data on the number of daily visits in 2014 reaching 500-800 people on weekdays and more than 2,000 people during the holiday season, the potential for organic waste reaches 55-88 kg/day on weekdays and 220 kg/day during the holiday season. This waste has not been utilized so it has the potential to cause unpleasant odors and reduce the aesthetics of the tourist area. Therefore, community service was carried out with the aim of transferring knowledge and skills to the young men and women of the AMGPM Cabang Luther Negeri Suli to process rujak fruit waste into liquid organic fertilizer (LOF). The methods used were socialization of knowledge about LOF, practical training in making POC, mentoring, and evaluation in the form of pre-tests and post-tests for 16 participants who took part in the activity to determine their understanding of the knowledge provided. The evaluation results of this activity showed that the level of knowledge and skills in processing waste into POC increased from 28.57% to 100%. The young men and women of Negeri Suli participated in the activity well, so they acquired new skills, actively participated in maintaining the cleanliness of the tourist area, while also gaining economic added value from the products produced.